Severe Postpartum Hemorrhage from Uterine Atony: A Multicentric Study - Carlos Montufar-Rueda; Laritza Rodriguez; José Douglas Jarquin; Alejandra Barboza; Maura Carolina Bustillo; Flor Marin; Guillermo Ortiz; Francisco Estrada (Journal of Pregnancy, 2013)
Objective. Postpartum hemorrhage (PPH) is an important cause of maternal mortality (MM) around the world. Seventy percent of the PPH corresponds to uterine atony. The objective of our study was to evaluate multicenter PPH cases during a 10-month period, and evaluate severe postpartum hemorrhage management. Study Design. The study population is a cohort of vaginal delivery and cesarean section patients with severe postpartum hemorrhage secondary to uterine atony. The study was designed as a descriptive, prospective, longitudinal, and multicenter study, during 10 months in 13 teaching hospitals. Results. Total live births during the study period were 124,019 with 218 patients (0.17%) with severe postpartum hemorrhage (SPHH). Total maternal deaths were 8, for mortality rate of 3.6% and a MM rate of 6.45/100,000 live births (LB). Maternal deaths were associated with inadequate transfusion therapy. Conclusions. In all patients with severe hemorrhage and subsequent hypovolemic shock, the most important therapy is intravascular volume resuscitation, to reduce the possibility of target organ damage and death. Similarly, the current proposals of transfusion therapy in severe or massive hemorrhage point to early transfusion of blood products and use of fresh frozen plasma, in addition to packed red blood cells, to prevent maternal deaths.